2017
DOI: 10.1016/j.cell.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for a Safety-Belt Mechanism That Anchors Condensin to Chromosomes

Abstract: SummaryCondensin protein complexes coordinate the formation of mitotic chromosomes and thereby ensure the successful segregation of replicated genomes. Insights into how condensin complexes bind to chromosomes and alter their topology are essential for understanding the molecular principles behind the large-scale chromatin rearrangements that take place during cell divisions. Here, we identify a direct DNA-binding site in the eukaryotic condensin complex, which is formed by its Ycg1Cnd3 HEAT-repeat and Brn1Cnd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
235
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(250 citation statements)
references
References 72 publications
11
235
2
Order By: Relevance
“…The colored circles indicate residues of hCAP‐H that interact with hCAP‐G (orange) and residues of BRN1 that interact with YCG1 (purple) or dsDNA (red). BC1, BC2, latch, and buckle regions defined by Kschonsak et al , and motifs III and IV of CAP‐H are also shown in Fig A.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The colored circles indicate residues of hCAP‐H that interact with hCAP‐G (orange) and residues of BRN1 that interact with YCG1 (purple) or dsDNA (red). BC1, BC2, latch, and buckle regions defined by Kschonsak et al , and motifs III and IV of CAP‐H are also shown in Fig A.…”
Section: Resultsmentioning
confidence: 66%
“…Residues of YCG1 that interact with BRN1 and dsDNA are labeled with light blue and red, respectively. The YC1 and YC2 regions indicate residues essential for DNA binding defined by Kschonsak et al . Structure‐based sequence alignment of hCAP‐H, XCAP‐H, and BRN1. The secondary structural elements of hCAP‐H and BRN1 are drawn above and below the sequence alignments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To specifically test the requirement for the Ycg1–Brn1 DNA‐binding groove, we repeated the experiment with a version of the condensin holocomplex that contains charge‐reversal mutations in the DNA‐binding groove. This mutant can still hydrolyse ATP, but its ATPase activity is not stimulated by the presence of DNA (Kschonsak et al , ). Consistent with the result for the tetrameric complex, this complex was also unable to induce DNA compaction in our assay (Fig EV3B).…”
Section: Resultsmentioning
confidence: 99%
“…If the interaction of condensin with DNA would only be topological, loop extrusion would not work, as DNA can slip out of the ring, which certainly will happen under an applied force. Our finding that a direct (electrostatic) contact between condensin and DNA is required to maintain the compacted state of DNA suggests that such a contact might serve as an anchor site at the base of a forming loop (Kschonsak et al , ). The finding that halfway compacted DNA molecules can eventually compact fully without the addition of extra protein is furthermore easy to imagine for a motor extruding a loop of ever‐larger size.…”
Section: Discussionmentioning
confidence: 97%
“…HEAT domains are also involved in binding and transporting protein ligands within the inner channel of the superhelix . More recently, this channel has been identified as a nucleic acid binding surface in a set of proteins with diverse functions, including RNA nuclear export, regulation of mRNA stability, and chromosome segregation …”
Section: Introductionmentioning
confidence: 99%